Exploring the pattern of internal communication in total quality management implementation in manufacturing companies - Samsudin, Sharina; Mohd Jalil, Nor Hayati; Ibrahim, Marzura (EDP Sciences, 2017)
Communication is an important aspect of organizational dynamic process and it is irrefutable one of the critical success factors of the Total Quality Management (TQM) implementation. Although there are increasing awareness concerning the importance of internal organizational communication, knowledge appears to have rarely translated into practice or there is lack of guidance to effectively practicing it.Therefore, a study was proposed to investigate the pattern of internal communication practice in TQM implementation.This paper concerns on focusing into internal communication practices in TQM implementation factors and the communication patterns in terms of message forms and mediums of communication to convey TQM messages.Reliability and Factor analysis were carried out to confirm items that form each factor in internal communication in TQM implementation.Based on the analysis of survey questionnaires distributed to 104 large manufacturing companies implementing TQM in Malaysia, it was found that there are certain communication patterns practice by the management when conveying and disseminating TQM messages, but they have no specific guidelines.Therefore, the internal communication practices are not well planned.Finally, it is suggested that further research should be carried out to explain clearly the role and strategy of communication on this issue in order to boost the success of TQM implementation particularly in manufacturing company.